População em situação de rua : desvendando olhares das razões vulneráveis. - Massavi, Viviane da Silva (2017)
The phenomenon "people in a street situation" did not arise or was restricted to capitalist societies, however, in history it is perceived that in this system the problem of poverty has worsened. The condition of the street situation transforms the life of any social subject, the changes permeate his or her way of looking at the other and himself, society treats him in an almost non-human way. In the imminence of the need to contribute scientifically to the study of this reality, this masters research in the area of Education, line of research Political Social Movements and Popular Education brings the proposal to give voice to a person in a street situation to describe How he sees himself and sees the world around him, in order to understand the mechanisms that oppress him and that provokes his invisibility or his visibility from patterns of colonization and his reification, through a dense description of the experience of this experience . People on the street have become a life unworthy of being lived, that is, a life that can be killed under apathy and social permissiveness, in this condition they become invisible to the law and society enabling acts of cruelty of all kinds. How to survive this concentration camp that the street has become? The question to be understood is challenging because it makes us think about how these mechanisms work in us, in society as a whole, that favor our almost complete indifference to this population, to the point of not bothering with their social abandonment. Believing that one of the possibilities for response would be a form of banality of evil, since there is no concern to intervene in this situation, in fact there is an implied consent of a desire to abbreviate their existence. Reinforcing the thesis that they are lives unworthy of being lived, denying them humanity. For the accomplishment of the research we opted for a qualitative study of phenomenological orientation based on Merleau- Ponty in the comprehensive analysis of this reality.